Knowledge of Family Health Strategy professionals regarding the Academia da Cidade Program (ACP) in the city of Recife - Moura, Vanessa (2016)
The aim of this study was to assess the knowledge of Family Health Strategy (FHS) professionals regarding the Academia da Cidade Program (ACP) in Recife. This is a descriptive, cross-sectional study using a quantitative approach at family health units (FHUs) in Recife, located at most 2 km from ACP centers. A total of 203 FHS professionals participated in the research. The data collection instrument consisted of a self-applied questionnaire. The variables investigated were related to sociodemographic and professional training aspects and knowledge of the ACP. Data collection occurred between July and August 2015, in pre-arranged visits at FHUs. The data were tabulated using the EpiDataEntry program and SPSS software. Of the professionals interviewed, 89.2% were women, 37% were aged between 30 and 39 years, 95% reported knowing the ACP, 76.5% knew the centers in their district, and 48.4% declared that they knew the objectives of the program. On the other hand, other than the centers, 58.9% do not know other locations where ACP activities are held or all the activities promoted by the Program. Thus, it was found that the FHS professionals are familiar with the ACP and its objectives, as well as the centers in their health district. However, fewer than half know other locations where the program functions, such as FHUs, in addition to recognizing only some of the activities as belonging to the ACP. Thus, there are important aspects that should be considered in order to improve integration between these services.